The Effect of Work Motivation and Work Discipline on Employee Performance Through Job Satisfaction Mediation - Budiarkah, Budiarkah; Sunaryo, Widodo; Yusnita, Nancy (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
The Influence of Work Motivation and Work Discipline on Employee Performance Through Mediation of Job Satisfaction (Empirical Study of Regional Water Supply Companies (Perumdam) Tjm, Bogor Regency). The purpose of this study was to determine the effect of work motivation and work discipline on employee performance through the mediation of job satisfaction. The study population was 161 employees of the executive division at the Regional Public Water Company (Perumdam) TJM Sukabumi Regency and a sample of 115 employees. Data collection for each variable studied using a questionnaire with a rating scale. Data analysis techniques using descriptive statistical analysis techniques and path analysis techniques (path analysis). The results showed: (a) There is a direct influence between work motivation on job satisfaction with a regression coefficient value of βy.1 = 0.986, work motivation contributes 97.21% to job satisfaction, (b) There is a direct effect between work discipline on job satisfaction with a regression coefficient value of βy.1 = 0.335. Work discipline contributes 11.22% to job satisfaction, (c). There is a direct influence between work motivation on employee performance with a regression coefficient value of βz.1 = 0.329. Work motivation contributes 10.82% to employee performance, (d). There is a direct effect between work discipline on employee performance with a regression coefficient value of βz.2 = 0.804. Work discipline contributes 64.64% to employee performance, (e). There is a direct effect of job satisfaction on employee performance with a regression coefficient of βz.y = 0.303. Job satisfaction contributes 9.18% to employee performance, (f). There is an indirect effect between work motivation on employee performance through job satisfaction with a zcount value greater than ztable or 38.42 > 1.96. So it can be concluded that job satisfaction mediates the influence of work motivation on employee performance, and (g). There is an indirect effect between work discipline on employee performance through job satisfaction with a zcount value greater than ztable or 15.02 > 1.96. So it can be concluded that job satisfaction mediates the effect of work discipline on employee performance.